SCREENING HANDLING SYSTEM BY REQUEST SONGS IN THE RADIO STAR 106.5FM - Susan Damayanti; Ir. Fitri Sjafrina, MMSI (Jurnal Sistem Informasi, 2000)
Star request is one of the best programs broadcast by Radio Star. In this event, the song playing is the most popular songs by request and pemutarannya done every data request, this time the radio Star still uses batch processing system manually. Microsoft Access is an application that is used to process data consisting of tables, forms, queries and reports. This table is used to accommodate incoming data to the event and the input through the form. The existence of computerization with microsoft applications in the handling of data access requests is expected to provide the best service so that it can attract more listeners to participate in the event and directly affects the development of Star Radio.